Efficacy and safety of CAR T-cell therapy in patients with primary or secondary CNS lymphoma: a study on behalf of the EBMT and the GoCART coalition - Ossami Saidy, Anna; Peczynski, Christophe; Thieblemont, Catherine; Daskalakis, Michael; Wehrli, Marc; Beauvais, David; Finke, Jürgen; Schorb, Elisabeth; Vandenberghe, Peter; Berning, Philipp; Stelljes, Matthias; Ayuk, Francis; et al. (HemaSphere, 2025)
Patients with relapsed or refractory (r/r) primary central nervous system (CNS) lymphoma (PCNSL) or secondary central nervous system (CNS) lymphoma (SCNSL) face a dismal prognosis. They have been excluded from most clinical CAR T-cell trials as investigators feared an increased risk for severe immune effector cell-associated neurotoxicity (ICANS). To investigate the potential of anti-CD19 CAR T-cell therapy (CART) in such patients, we analyzed data of 100 patients with CNS manifestation treated with CART between January 2018 and July 2023 and reported to European Society for Blood and Marrow Transplantation. Median age was 62 years. Of patients, 58% had failed ≥3 treatment lines, and 40% had received autologous stem-cell transplantation before CART. Fifty-nine patients received axicabtagene ciloleucel, 38 patients were treated with tisagenlecleucel, three patients received other products. At the time of CART, 67 patients had active CNS disease. Overall and progression-free survival (PFS) at 24 months were 37% and 28%. Relapse incidence (RI) at 24 months was 59%, whereas non-relapse mortality at 1 year was 7%. Cytokine release syndrome (CRS) and ICANS of any grade occurred in 83% and 42% of patients, respectively. CRS grade 3 occurred in 11 and ICANS grades 3-4 in 17 patients. Two patients died of neurotoxicity. Elevated lactate dehydrogenase was an independent risk factor for RI and PFS (hazard ratio [HR] 2.4, p = 0.003; HR: 1.9, p = 0.016). Patients with ECOG 2-3 had a significantly increased risk for the development of ICANS (HR 2.68, p = 0.002). These data support the implementation of CART as treatment for patients with r/r PCNSL and SCNSL.
Gesehen am 19.11.2025